2016
DOI: 10.3889/oamjms.2016.093
|View full text |Cite
|
Sign up to set email alerts
|

A Worksite Health Education Workshop as Empowerment Intervention for Health Promotion in the National Research Centre of Egypt

Abstract: AIM:The study aimed to assess worksite health education workshops as a successful tool for health promotion of employees.MATERIAL AND METHODS:A one day workshop was held for individuals engaged in research activities in the National research Centre of Egypt at the worksite. Its main objective was to highlight the nature, causes, symptoms and management of job stress. Participants were asked to fill a personality assessment sheet, a self-reported questionnaire for job satisfaction. Other questionnaires for asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…One similar study conducted by Amer et al, (2016) [ 23 ] on researchers working at NRC in Egypt showed that those who didn’t receive their PhD/MD had a significantly higher score on Falsification of Type scale compared to PhD/MD holders. Falsification of type score also showed a significant negative correlation with income among researchers in the same study.…”
Section: Discussionmentioning
confidence: 90%
“…One similar study conducted by Amer et al, (2016) [ 23 ] on researchers working at NRC in Egypt showed that those who didn’t receive their PhD/MD had a significantly higher score on Falsification of Type scale compared to PhD/MD holders. Falsification of type score also showed a significant negative correlation with income among researchers in the same study.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, parental psychosocial adjustment [37] has proven a cardinal influence on the family support, thereby causing a significant qualityof-life improvement for their children [38]. Stress has been detected among many populations in Egypt including females, low-income families, and some specific jobs and professions like employees over workers, researchers, and cotton industry workforce in weaving and spinning [39][40][41][42][43][44]. Besides, the pandemic came to worsen the case and aggravate the mental health condition to target more vulnerable populations like housewives and the youth under 44 years in age.…”
Section: Discussionmentioning
confidence: 99%